Pengaruh Kepuasan Penumpang terhadap Kualitas Pelayanan Maskapai Garuda Indonesia di Bandar Udara Abdulrachman Saleh Malang - Febriansyah Ignas Pradana; Yuninda Zahra Ariyanti (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Garuda Indonesia airline in dealing with the Covid-19 pandemic implemented Physical Distancing as a prevention of the transmission of the Covid-19 this was a form of quality service provided to passengers. This study aims to determine passenger satisfaction with the service quality of Garuda Indonesia Airlines and determine the service quality attributes that can be developed by Garuda Indonesia Airlines. This study uses quantitative methods, in this case, to determine passenger satisfaction, Servqual and IPA (Importance Performance Analysis) data processing is used to compare passenger expectations and perceptions. The results of the research on the service quality of the Garuda Indonesia airline show that the service quality is in accordance with the expectations of the passengers, so it can be concluded that the service quality of the Garuda Indonesia airline is good. Keywords : Malang Abdulrachman Saleh Airport, Garuda Indonesia Airlines, Service Quality, Passanger Satisfaction